PARAMETERS OPTIMIZATION OF HIGH FREQUENCY ULTRASONIC SYSTEM FOR WIRE BONDING - I. B. Petuhov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Mathematical equations for resonant frequency and impedance of ultrasonic transducer for wire bonding were proposed. Clamping optimization of bonding tool was determined due to modelling of resonant frequency and impedance for standard and high frequency ultrasonic vibrations in ultrasonic system. It was shown that proposed technique gives good fit to the experimental data.